Ustekinumab induces fast response and maintenance of very severe refractory scalp psoriasis: results in two Greek patients from the psoriasis hospital-based clinic. - Papadavid, E; Ferra, D; Koumaki, D; Dalamaga, M; Stamou, C; Theodoropoulos, K; Rigopoulos, D (Dermatology, 2014)
BACKGROUND: Scalp psoriasis, one of the most common sites of psoriasis involvement, is often difficult to control with topical agents. There is a lack of substantial evidence-based data for the efficacy and safety of systemic therapies. METHODS: Two patients from our university-based psoriasis clinic with chronic plaque psoriasis and severe recalcitrant scalp involvement were assessed by Psoriasis Area and Severity Index and Psoriasis Scalp Severity Index scores, respectively, and quality of life by the Dermatology Life Quality Index. RESULTS: We report 2 psoriasis patients with very severe scalp psoriasis who developed a fast clinical response of scalp psoriasis to ustekinumab in 8 weeks with excellent patient adherence up to 28 weeks of follow-up and positive impact on quality of life due to rapid and long-term clearing. CONCLUSION: Ustekinumab produces a fast clinical response of recalcitrant scalp psoriasis with excellent patient adherence and a positive impact on quality of life due to rapid and long-term clearing in patients with very severe scalp involvement who failed conventional topical and systemic treatment.
Keywords: Aged; Antibodies, Monoclonal, Humanized; Dermatologic Agents; Female; Greece; Hospitals, University; Humans; Middle Aged; Outpatient Clinics, Hospital; psoriasis; Quality of Life; Scalp Dermatoses; Severity of Illness Index; Treatment Outcome; Ustekinumab